EVALUATION OF SERUM VITAMIN B12 AND FOLIC ACID IN PATIENTS WITH ACUTE MYOCARDIAL INFARCTION AMONG SUDANESE’S PATIENT’S - Bilal. A. Bilal, Mohammed; Hamid, Tarig.A.M.; Gadir, Makaawi A.; Mahmoud, Mihad.M. (Journal of Biomedical and Pharmaceutical Research, 2021)
The Sudanese population has high rate of coronary artery disease (CAD). The potential association between deficiency of vitamin B12 and folic acid, in patients with acute myocardial infarction (AMI), where investigated previously with conflicted results. A case-control study was carried out involving 60 AMI patients (age 39–87 years; 40 men and 20 women) and 40 normal healthy individuals (age 39–84 years; 20 men and 20 women). Fasting venous blood samples were obtained from patients and controls. Serum was analyzed for vitamin B12 and folic acid using radio assays. The mean concentration of serum B12 and folate in AMI patients were found to be significantly lower than in controls. Vitamin B12 and folate deficiency may be considered as a risk factor for CAD development.